The Adaptation of the Moral Integrity Scale into Turkish and Analysis of the Psychometric Features - Okan, Nesrullah; Eksi, Halil (My University, 2020)
The aim of this study is to adapt the Moral Integrity Scale developed by Sclenker (2008) to Turkish and conduct its psychometric analysis. The scale items were translated into Turkish by five specialists in the first place. After the language structure, culture suitability and understandability of the items were examined by the two experts, the items agreed upon were translated back to their original language by the two translation experts. After the positive evaluations of the experts, the final version of the scale items was decided. During the adaptation process of the study, data were collected from 470 people for exploratory factor analysis; from 248 people for confirmatory factor analysis and from 100 people for criterion validity. In this context, Exploratory Factor Analysis (AFA) was used to test the construct validity of the scale first. As a result of the exploratory factor analysis, it is seen that the moral integrity scale explains 52,127% of the variance as one dimension. Confirmatory factor analysis (CFA) was then performed to test the construct validity of the scale. The one-dimensional and 18-item structure of the Moral Integrity Scale was analyzed with DFA and accepted fit indices were obtained (X2 / sd = 2.745; p <.001; RMSEA = 0.061; S-RMR = 0.051; NFI = 0.929; CFI = 0.954; GFI = 0.915; RFI = 0.919). In order to calculate the scale reliability, the Cronbach Alpha (?) internal consistency coefficients and the difference between the lower and upper scores of 27% were examined. For the Moral Integrity Scale, the internal consistency coefficient Cronbach’s Alpha value was determined as 961. At the same time, the moral identity scale was used for criterion validity and a significant positive relationship was obtained with the two sub-dimensions of this scale. The total score obtained from the scale gives the person’s moral integrity score. According to all these results, it is understood that the Moral Integrity Scale has sufficient validity and reliability values.
Keywords: Psikoloji